Spaced Training Enhances Contextual Fear Memory via Activating Hippocampal 5-HT2A Receptors - Jiang, Lizhu; Wang, Liping; Yin, Yan; Huo, Mengke; Liu, Chao; Zhou, Qixin; Yu, Dafu; Xu, Lin; Mao, Rongrong (Frontiers in Molecular Neuroscience, 2020)
Spaced training is robustly superior to massed training, which is a well-documented phenomenon in humans and animals. However, the mechanisms underlying the spacing effect still remain unclear. We have reported previously that spacing training exerts memory-enhancing effects by inhibiting forgetting via decreasing hippocampal Rac1 activity. Here, using contextual fear conditioning in rat, we found that spaced but not massed training increased hippocampal 5-HT2A receptors’ expression. Furthermore, hippocampal administration of 5-HT2A receptor antagonist MDL11939 before spaced training blocked the enhanced memory, while hippocampal administration of 5-HT2A receptor agonist TCB-2 before massed training promoted the memory. Moreover, MDL11939 activated hippocampal Rac1, while TCB-2 decreased hippocampal Rac1 activity in naïve rats. These results indicated the possibility of interaction between 5-HT2A receptors and Rac1, which was demonstrated by co-immunoprecipitation experiments. Our study first demonstrates that activation of hippocampal 5-HT2A is a mechanism underlying the spacing effect, and forgetting related molecular Rac1 is engaged in this process through interacting with 5-HT2A receptors, which suggest a promising strategy to modulate abnormal learning in cognitive disorders.